Eco-friendly PLA-kenaf fibre biocomposite for food packaging - Anuar, Hazleen; Kaiser, Mohammad Rejaul; Fuad, Faizah; Ahmad, Zuraida (2011)

(untitled)
From a statistics accounted in 1999, 48% of plastic bottle that used is made from PET. Among them a huge percentage are end up as garbage and caused the landfills. This toxic waste pollutes our subsurface water label through leaching. PLA is a strong candidate to substitute conventional petroleum based polymer. Kenaf fiber was added to reduce the cost as well as to increase properties. The mechanical and thermal properties shows that PLA-Kenaf biocomposite shows better properties than conventional food packaging polymer.